Chungkookjang, a soy food, fermented with Bacillus amyloliquefaciens protects gerbils against ishcmeic stroke injury, and post-stroke hyperglycemia. (February 2020) - Jeong, Do Yeon; Jeong, Seong-Yeop; Zhang, Ting; Wu, Xuangao; Qiu, Jing Yi; Park, Sunmin
Graphical abstract: Highlights: Chungkookjang, soybeans fermented with Bacillus amyloliquefaciens, had thrombolytic activity. Chungkookjang protected against neuronal cell death in gerbils with transient occlusion of the arteries. Chungkookjang alleviated short-term memory loss and neurological symptoms in stroke induced gerbils. Chungkookjang reduced proinflammatory cytokines and improved blood flow. Chungkookjang increased Bacteriodia and decreased Clostridia to similar profiles as the normal-control in the gut. Abstract: Chungkookjang is a traditional Korean fermented soybean food with anti-diabetic and thrombolytic activity. It may also have anti-stroke activity. We determined that chungkookjang made with Sunchang Research Center for Fermentation Microbes 100730 and 100731 strains of Bacillus amyloliquefaciens (SRCM100730; CKJ730) and SRCM100731(CKJ731) protected against ischemic stroke and post-stroke hyperglycemia in Mongolian gerbils with ischemic stroke induced by transient occlusion of the carotid arteries. Gerbil fed 4.5% cooked soybeans (CSB), CKJ730, CKJ731, or cellulose (negative-control) in 40 energy% fat diets for 3 weeks, and then had artery occlusion for 8 min and continued taking the assigned diet for 5 weeks. CKJ730 and CKJ731 had thrombolytic activity and prevented neuronal cell death. Consequently, they improved short-term memory and spontaneous alteration compared to the negative-control. CKJ730 and CKJ731 improved neurological symptoms including drooped eyes, crouched posture, flexor reflex, and walking patterns the most among the stroke-induced gerbils. CKJ730 and CKJ731 increased active time, grip strength, and blood flow measured by Doppler compared to the negative-control. CKJ730 protected against post-stroke glucose dysregulation by restoring β-cell mass in the gerbils with transient artery occlusion. Serum tumor necrosis factor-α and interleukin-1β levels were lower in CKJ730 and CKJ731 than the negative-control. CSB also improved glucose metabolism and suppressed inflammatory cytokines, but less than CKJ730 and CKJ731. Clostridia increased, and Bacteriodia slightly decreased in the negative-control group, compared to the normal-control. CKJ730 and CKJ731 changed the amounts of Bacteriodia and Clostridia to be similar to normal-control. In conclusion, the daily intake of chungkookjang fermented with B. amyloliquefaciens improved the gut microbiome, increased blood flow to the brain, suppressed systemic inflammation, and may reduce the susceptibility to injury from ischemic stroke in gerbils subjected to ischemic injury.